Interpreting Religion: The Case of Jihad - O'Donoghue, Michael (Australian religion studies review, 2009)
Scholars of religion and western Muslims have been accused of glossing over the aggressive interpretation of jihad in Islam in order to make the religion more palatable to a western audience. This paper argues that the accusation is based on a narrow understanding of the available hermeneutical strategies and, by exploring some of the interpretative tradition, highlights the point that religions are rich reservoirs of meaning developed in multiple contexts. As living traditions religions can, and do, call on different meanings from this reservoir.